Arctic laws - Pettersson, Lasse (Arctic Portal, 2011)
Dr. Lasse Pettersson, Nansen Environmental and Remote Sensing Center, Norway, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.